Excess worker turnover and fixed-term contracts: Causal evidence in a two-tier system - Mario Centeno; Alvaro A. Novo (Institute for the Study of Labor (IZA), 2011)
Portuguese firms engage in intense reallocation, most employers simultaneously hire and separate from workers, resulting in high excess worker turnover flows. These flows are constrained by the employment protection gap between open-ended and fixed-term contracts. We explore a reform that increased the employment protection of open-ended contracts and generated a quasi-experiment. The causal evidence points to an increase in the share and in the excess turnover of fixed-term contracts in treated firms. The excess turnover of open-ended contracts remained unchanged. This result is consistent with a high degree of substitution between open-ended and fixed-term contracts. At the firm level, we also show that excess turnover is quite heterogeneous and quantify its association with firm, match, and worker characteristics.
urn:nbn:de:101:1-201202285082
Keywords: J21; J23; J63; 330; excess worker turnover; two-tier systems; quasi-experiment; fixed-term contracts; Arbeitsmobilität; Arbeitsvertrag; Arbeitsverhältnis; Feldforschung; Portugal